Documental 3d y video sobre la evolución de la calle la Ronda en Quito - López Soto, Diego Fernando (2014)
The main idea of the film in 3D and video is to rescue the essence of the Quito identity through some of the most emblematic places in Quito, such as La Ronda Street, which is the most representative since colonial times. Since its inception this sector of Quito has had a transformation in several stages, so we have this street originated by filling a ravine. Later it was a place in which they lived several iconic characters from the society of the time, which was dominated by love of bohemian life, music, and poetry, giving origin to the Ecuadorian hall is the music that we identified to date... See the attached file